NIH Toolbox Cognition Battery (NIHTB-CB): List Sorting Test to Measure Working Memory. (24th June 2014) - Tulsky, David S.; Carlozzi, Noelle; Chiaravalloti, Nancy D.; Beaumont, Jennifer L.; Kisala, Pamela A.; Mungas, Dan; Conway, Kevin; Gershon, Richard
Abstract: The List Sorting Working Memory Test was designed to assess working memory (WM) as part of the NIH Toolbox Cognition Battery. List Sorting is a sequencing task requiring children and adults to sort and sequence stimuli that are presented visually and auditorily. Validation data are presented for 268 participants ages 20 to 85 years. A subset of participants ( N =89) was retested 7 to 21 days later. As expected, the List Sorting Test had moderately high correlations with other measures of working memory and executive functioning (convergent validity) but a low correlation with a test of receptive vocabulary (discriminant validity). Furthermore, List Sorting demonstrates expected changes over the age span and has excellent test–retest reliability. Collectively, these results provide initial support for the construct validity of the List Sorting Working Memory Measure as a measure of working memory. However, the relationship between the List Sorting Test and general executive function has yet to be determined. ( JINS, 2014, 20, 1–12)